ENT300 Black Forest Company / Fiqri Assyafiq Abu Bakar Sham... [et.al] - Abu Bakar Sham, Fiqri Assyafiq; Haidi, Siti Farhanah; Jumput, Jessifa Debra; Jahari, Mohd Noor Suffian; Belai, Jonicer Romie (2016)
Our business is owned actively by partnership of 5 partners, which incorporated as D.i.Y or more known as Do It Yourselves. Our business provide reuse material or product that being innovated into something new that can be use by teenager’s, middle age and elderly.